Clinical characteristics and prognostic analysis of acute necrotizing encephalopathy of childhood: a retrospective study at a single center in China over 3 years - Fang, Yu; Gao, Qiqi; Jin, Wenwen; Li, Jianshun; Yuan, Hao; Lin, Zhenlang; Pan, Guoquan; Lin, Wei (Frontiers in Neurology, 2023)
Objective Acute Necrotizing Encephalopathy of Childhood (ANEC) is a rare, fulminant neurological disease in children with unknown mechanisms and etiology. This study summarized the clinical characteristics, treatment, and prognosis of ANEC through a retrospective analysis, providing insights into the ANEC early diagnosis and prognosis assessment. Methods Clinical data of children diagnosed with ANEC at the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University from July 1, 2020, to June 30, 2023, were retrospectively analyzed. Results There were 25 cases, 14 males and 11 females, with a median age of 3 years. Hospital admissions were mainly in the winter (14/25, 56%) and spring (9/25, 36%). All patients presented with varying degrees of fever and altered consciousness, with 92% (23/25) experiencing high body temperatures (>39.1°C) and 88% (22/25) having a Glasgow coma scale (GCS) score of ≤8. Seizures were observed in 88% (22/25) of patients. Laboratory findings indicated 100% B lymphocyte activation (14/14), and 78% (14/18) of patients showed cytokine storm (interleukin (IL)-6, IL-8, IL-10, interferon (IFN)-α). Neuroimaging showed symmetrical thalamus involvement, commonly involving basal ganglia and brainstem regions. Viral infection (23/24, 96%) was the predominant etiological finding, with 42% (10/24) of cases due to SARS-CoV-2 infection and 42% (10/24) to influenza A virus infection. Multi-organ dysfunction occurred in 68% (17/25) of patients, and 52% (13/25) died. Correlation analysis revealed the death group exhibited higher proportion of male, lower GCS scores, higher IL-6 level and a greater likelihood of associated brainstem impairment (p < 0.05). Conclusion ANEC is more prevalent in the winter and spring, and its etiology may be associated with B lymphocyte activation and cytokine storm following viral infections. Clinical manifestations lack specific features, with fever, consciousness disturbances, and seizures being the main presentations, particularly in cases of high fever and hyperpyrexia. ANEC progresses rapidly and has a high mortality rate. The child’s gender, GCS score, IL-6 levels, and the presence of brainstem involvement can serve as important risk factors for assessing the risk of mortality.